Work-Related Risk Factors for Rotator Cuff Syndrome in a Prospective Study of Manufacturing and Healthcare Workers. (May 2023) - Meyers, Alysha R.; Wurzelbacher, Steven J.; Krieg, Edward F.; Ramsey, Jessica G.; Crombie, Kenneth; Christianson, Annette L.; Luo, Lian; Burt, Susan
Objective: This prospective study assessed the risk of developing rotator cuff syndrome (RCS) with separate or specific combinations of biomechanical exposures measures, controlling for individual confounders. Background: Compared with other musculoskeletal disorders, rates of work-related shoulder musculoskeletal disorders have been declining more slowly. Method: We conducted up to 2 years of individual, annual assessments of covariates, exposures, and health outcomes for 393 U.S. manufacturing and healthcare workers without RCS at baseline. Task-level biomechanical exposures assessed exposure to forceful exertions (level, exertion rates, duty cycles), vibration, and upper arm postures (flexion, abduction). Hazard ratios (HRs) were calculated with Cox proportional hazard models. Results: We observed 39 incident RCS cases in 694 person-years (incidence rate = 5.62 per 100 person-years). Adjusting for confounders, we found increased risk of incident RCS associated with forceful hand exertions per minute for three upper arm posture tertiles: flexion ≥45° (≥28.2% time, HR = 1.11, CI [1.01, 1.22]), abduction ≥30° (11.9–21.2%-time, HR = 1.18, CI [1.04, 1.34]), and abduction >60° (≥4.8% time, HR = 1.16, CI [1.04, 1.29]). We failed to observe statistically significant effects for other interactions or any separate measures of biomechanical exposure. Conclusion: This study highlights the importance of assessing combinations of exposure to forceful repetition and upper arm elevation when developing interventions for preventing RCS. Application: Based on these results, interventions that reduce exposure to forceful repetition (i.e., lower force levels and/or slower exertion rates) may reduce the risk of RCS, especially when upper arm elevation cannot be avoided.